Engineering Mathematics. - Ram, Babu (Pearson, 2009)
Engineering Mathematics covers the four mathematics papers that are offered to undergraduate students of engineering. With an emphasis on problem-solving techniques and engineering applications, as well as detailed explanations of the mathematical concepts, this book will give the students a complete grasp of the mathematical skills that are needed by engineers.